Resilience Among Indigenous Graduate Nursing Students: A Scoping Review - Sedgwick, Monique; Crosschild, Chloe; Rohatinsky, Noelle; Scott, David (Quality Advancement in Nursing Education / Avancées en formation infirmière)

(untitled) (Canadian Association of Schools of Nursing / Association canadienne des écoles de sciences infirmières, 2025)
Aim: The aim of this scoping review was to systematically assemble, examine, and map the extant literature pertaining to the resilience among Indigenous nursing students in graduate programs.Background: Although graduate preparation for health care professionals positively influences the health outcomes of recipients of care through participation in decision-making, advanced practice roles, education, policy development, and research, colonial frameworks present in the form of institutional or program-related barriers limit the number of Indigenous students to access graduate nursing programs. Moreover, entrenched Euro-Western epistemology and ontology that privilege certain knowledges and ways of knowing reinforce the understanding of resilience as being outcomes-based. Resilience among Indigenous Peoples, however, embraces ideas of transformation and adaptation that incorporate complex social dynamics and interpersonal processes that foster movement towards well-being, healing, and growth.Design: A scoping review was conducted using the Arksey and O’Malley (2005) and the PRISMA-ScR (Preferred Reporting Items for Systematic Reviews and Meta-analyses Extension for Scoping Reviews) framework (Moher et al., 2009) guided the reporting.Method: Six databases were searched for relevant articles by a health sciences librarian. This was supplemented by hand searches and internet searches for grey literature. A total of 708 results published between 2000 and 2023 were retrieved from the six database searches. Following title and abstract screening, a total of 88 full-text articles were independently reviewed, resulting in two items for inclusion in the study.Results: Two themes were identified from the review that may tangentially influence resilience among Indigenous graduate nursing students: identity and biculturalism. Gaps in the literature included limited global literature on resilience; no exploration of the explicit experience of resilience; study samples and populations frequently merging Indigenous students with marginalized students and Black and other racialized students, making it difficult to link findings with specific groups of participants; and reporting of support program development and evaluation of these programs.Conclusion: This review highlighted that research on Indigenous graduate nursing students’ experience of resilience is lacking. Moreover, concepts such as biculturalism perpetuate a dichotomous and colonial understanding of Indigenous graduate nursing students’ experience of resilience.Relevance to Universities and Nursing Education Programs: While strategies such as transition programs and talking circles are valuable as initial steps, governance approaches that produce program- and university-wide policies must be reconceptualized. While inclusion policies benefit student completion and retention rates, these policies do little to transform the academy. We suggest an Indigenous board of governors comprising Elders, local Indigenous scholars and educators, and Indigenous students whose mandate is to develop, implement, and oversee policies and practices that directly affect Indigenous students and allow them to become part of universities’ governance models.